Adaptive reconfiguration of the human NK‐cell compartment in response to cytomegalovirus: A different perspective of the host‐pathogen interaction. Issue 5 (25th April 2013) - Muntasell, Aura; Vilches, Carlos; Angulo, Ana; López‐Botet, Miguel
<x xml:space="preserve">Abstract</x> As discussed in this review, human cytomegalovirus (HCMV) infection in healthy individuals is associated with a variable and persistent increase of NK cells expressing the CD94/NKG2C activating receptor. The expansion of NKG2C+ NK cells reported in other infectious diseases is systematically associated with HCMV co‐infection. The functionally mature NKG2Cbright NK‐cell subset expanding in HCMV+ individuals displays inhibitory Ig‐like receptors (KIR and LILRB1) specific for self HLA class I, and low levels of NKp46 and NKp30 activating receptors. Such reconfiguration of the NK‐cell compartment appears particularly marked in immunocompromised patients and in children with symptomatic congenital infection, thus suggesting that its magnitude may be inversely related with the efficiency of the T‐cell‐mediated response. This effect of HCMV infection is reminiscent of the pattern of response of murine Ly49H+ NK cells against murine CMV (MCMV), and it has been hypothesized that a cognate interaction of the CD94/NKG2C receptor with HCMV‐infected cells may drive the expansion of the corresponding NK‐cell subset. Yet, the precise role of NKG2C+ cells in the control of HCMV infection, the molecular mechanisms underlying the NK‐cell compartment redistribution, as well as its putative influence in the response to other pathogens and tumors remain open issues.